UTILISATION DES REPRESENTATIONS INITIALES POUR AMELIORER L’APPRENTISSAGE DES ELEVES DE SECONDE EN SVT - Attrassi, Khaled; Haimed, Mohamed (European Scientific Journal, ESJ, 2015)
A representation is a thought structure under - lying in a simple explanatory model, logical and organized whose origins are diverse, which can be used in a situation to ask or solve a problem. Following a remark being with students, we became aware of their own representations of biological and geological processes, results of their sociocultural environments and lessons issued previously. So we realized that we can not be ignored in progress, if we want the students acquire knowledge sustainably. Thus, it has made several collections of initial representations on different notions of second program. After analyzing these results, it emerged several obstacles to learning. Due to time constraints, it has been put into practice in our class two methods to overcome these obstacles and to change the students’ designs. On the one hand, students compared their performances with each other and on the other hand, another concept, they shared their knowledge representations built. Analysis of the production obtained in the short, medium and long term allows to highlight the impact of the use of initial representations in sustainable learning.